Investigating subsurface damages in semiconductor–insulator–semiconductor solar cells with THz spectroscopy - Blumroeder, Ulrike; Hempel, Hannes; Fuechsel, Kevin; Hoyer, Patrick; Bingel, Astrid; Eichberger, Rainer; Unold, Thomas; Nolte, Stefan (physica status solidi (a), 2017)
The influence of near-surface crystal damage on carrier dynamics in silicon has been investigated with optical-pump THz-probe and THz emission studies. The surface damage is caused by a plasma process used for the fabrication of the ultrathin insulator within semiconductor–insulator–semiconductor (SIS) solar cells. The ion bombardment during the plasma process introduces a highly damaged subsurface region. Furthermore, the integration of positive interface charges leads to the formation of a depletion region that can be detected via the emitted THz radiation. The results are compared with classic I–U-characterization demonstrating that THz spectroscopy can be used as a supplementary tool for the investigation of process-induced surface damages.
CRIS-Team Scopus Importer:2023-04-20
Keywords: optical-pump THz-probe; Solar cell; surface charges; surface damage; THz emission